Improving Students’ Learning Outcomes Using 4Me Module with Cooperative Learning - Endang Suprapti; Himmatul Mursyidah; Siti Inganah (SAINTIS Publishing, 2018)
Based on the evaluation result on the course of linear algebra, the result of mathematics student’s learning outcome, faculty of teacher training and education, University of Muhammadiyah Surabaya, from 26 students indicate that 30,76 % of students complete learning and 69,24% did not complete the target with average value 55,60. Based on the student's opinion, the course of linear algebra was difficult because has a high difficulty level, the learning system uses direct learning, and it causes the boredom. Furthermore, the reference material does not support completely for linear algebra. Thus we need additional learning models, so the students do not get bored and difficult by direct learning model that we used. In this case, we use “The Cooperative Learning Type TPS” model with 4 Me module in order to help the student to be able to work and shared with their friend to find problem solutions so that the interaction among learners occurs and the learning process becomes more active. We use the classroom action research method in this research. Based on the result of the research, we can improve 30% student’s learning result, 21 % of student’s activity and 95 % positive student’s response.